SPESIASI DAN BIOAVAILABILITAS LOGAM BERAT Cu DAN Zn DALAM TANAH PERTANIAN ORGANIK DI DAERAH BEDUGUL - Tri Rahayu; I Made Siaka; Ida Ayu Gede Widihati (Jurnal Kimia (Journal of Chemistry), 2015)
A research on heavy metal speciation and bioavailability of Cu and Zn in soil of organic agriculture in Bedugul area has been carried out. This study aimed to determine the total metal content, speciation, and bioavailability of Cu and Zn in the soil of organic agriculture aged 5 and 4 years in Bedugul area. The total metal content was performed by the used of a digestion method with a mixture of HNO3 and HCl (3:1) in the ultrasonic bath and followed by heating on the hotplate. Speciation and bioavailability of Cu and Zn was conducted using SET (Sequential Extraction Technique). The content of Cu and Zn in the total sample was analyzed using the Atomic Absorption Spectrophotometer (AAS) with a calibration curve method. The total metal concentrations of Cu in the organic agricultural land of aged 5 and 4 years and were 41.8808-49.1060 mg/kg and 22.8544-41.6616 mg/kg  whereas the concentrations of Zn  in the organic agricultural land of aged 5 and 4 years were 62.9273-73.3729 mg/kg and 58.0970-73.9987 mg/kg respectively. The speciation of Cu obtained in in the organic agricultural land of aged 5 and 4 years was ranged from 6-17% and 3-14% in the EFLE fraction, from 9 to 37% and 6 to 24%  in the Fe/Mn oxides fraction, and ranged from 27 to 53% and 41 to 69% in the resistant fraction (non bioavailable). The Zn speciation found in the organic agricultural land of aged 5 and 4 years was ranged from 6 to 9% and 7 to 10% the EFLE fraction (bioavailable), from 15 to 22% and 11 to 25% in the Fe/Mn oxides and organic (potentially bioavailable) fractions and ranged from 46 to58% and 40 to 53%  in the silicate fraction (non bioavailable).